Original in: Schiller Nationalmuseum/Deutsches Literaturarchiv. In Belgium? Place of persons indicated on front. Von Wiegand of the U.S. Sun, Captain Fortescue of U.S. America
Original in: Schiller Nationalmuseum/Deutsches Literaturarchiv. In Belgium? Place of persons indicated on front. Von Wiegand of the U.S. Sun, Captain Fortescue of U.S. America.